Structure and crystallization of SiO2 and B2O3 doped lithium disilicate glasses from theory and experiment. Issue 37 (13th September 2017) - Erlebach, Andreas; Thieme, Katrin; Sierka, Marek; Rüssel, Christian
Abstract : Solid solutions of SiO2 and B2 O3 in Li2 O·2SiO2 are synthesized and characterized for the first time by calculations and experiments. Abstract : Solid solutions of SiO2 and B2 O3 in Li2 O·2SiO2 are synthesized and characterized for the first time. Their structure and crystallization mechanisms are investigated employing a combination of simulations at the density functional theory level and experiments on the crystallization of SiO2 and B2 O3 doped lithium disilicate glasses. The remarkable agreement of calculated and experimentally determined cell parameters reveals the preferential, kinetically controlled incorporation of [SiO4 ] and [BO4 ] at the Li + lattice sites of the Li2 O·2SiO2 crystal structure. While the addition of SiO2 increases the glass viscosity resulting in lower crystal growth velocities, glasses containing B2 O3 show a reduction of both viscosities and crystal growth velocities. These observations could be rationalized by a change of the chemical composition of the glass matrix surrounding the precipitated crystal phase during the course of crystallization, which leads to a deceleration of the attachment of building units required for further crystal growth at the liquid–crystal interface.